Assessing the contribution factors for the enhancement of green building index (GBI) in the Malaysian construction industry - Yeong, Liang Sim; Frederick Putuhena; Puong, Ling Law; Azhaili Baharun (Fakulti Kejuruteraan ,UKM,Bangi., 2015)
This research paper focuses on the several most crucial organisation factors that directly infl uence the Green Building Index (GBI) in the Malaysian construction industry. The fi ndings of the paper are based upon a comprehensive literature search and empirical studies conducted with 102 construction fi rms in Malaysia. All these fi rms are selected based on fi rm sizes of 50 people and above within the organisation. Seven internal organisation factors are correlated with fi ve external factors for the improvement of the green construction organisation. The study used Canonical correlation methods to correlate simultaneously the internal factors to the assessment of the improvement for the organisation. In summary it can be stated that the overall level of organisation factors are medium and there are rooms for improvement. The most important internal factors that infl uence the Malaysian construction projects were found to be ‘Environmental/Green Technology’, ‘Training’ and ‘resistance to change. The least important factors were documentation and usage of computer technology. On the other hand, external factors that infl uence projects green performance were found to be ‘Integration with Environmental Management’, ‘New Approaches to Management’ and ‘Shifting Customer Expectations’ The fi ndings suggest that the integration of several factors as the preferred option for the enhancement of the green performance within the Malaysian Construction Industry. Senior Management can utilise these factors to assess their strengths and weaknesses on the organisation practices necessary for the effective deployment in construction projects.